A Randomized, Double-blind, Active-controlled Phase III Trial of a Cell Culture-derived Quadrivalent Inactivated Influenza Vaccine in Healthy South Korean Children and Adolescents 6 Months to 18 Years of Age. Issue 9 (September 2019) - Eun, Byung Wook; Lee, Taek Jin; Lee, Jina; Kim, Ki Hwan; Kim, Dong Ho; Jo, Dae Sun; Shin, Sun Hee; Kim, Hun; Kim, Kyung-Ho; Kim, Yun-Kyung
Abstract : Background: Cell culture-derived influenza vaccines have several important advantages over egg-based influenza vaccines. The quadrivalent influenza vaccine may offer broader protection against seasonal influenza than trivalent influenza vaccine by containing 1 more B strain. The purpose of this study was to evaluate the immunogenicity and safety of NBP607-QIV, a novel cell culture-derived inactivated quadrivalent influenza vaccine (cIIV4), in children and adolescents. Methods: This phase III, randomized, double-blind, multicenter trial in children/adolescents (6 mo to 18 yr) was conducted in South Korea during 2014–2015 season. Subjects were randomized 4:1 to receive either NBP607-QIV or control inactivated trivalent influenza vaccine. Hemagglutination inhibition antibody titers were assessed in prevaccination and 28 days postvaccination sera. Safety data were collected for up to 6 months postvaccination. Results: A total of 454 participants completed the study. Three-hundred sixty-six subjects received cIIV4 and 88 subjects received inactivated trivalent influenza vaccine. Overall, NBP607-QIV met the immunogenicity criteria of Committee for Medicinal Products for Human Use for each of the 4 strains. Between the NBP607-QIV and control groups, immunogenicity endpoints were comparable. Participants younger than 3 years of age had lower immunologic responses to 2 influenza B strains in both NBP607-QIV and control group. No deaths, vaccine-related serious adverse events (AEs) or withdrawals because of AEs were reported. The solicited AEs reported were generally of mild intensity. Conclusions: NBP607-QIV, a novel cIIV4, showed good immunogenicity to all 4 influenza strains and had tolerable safety profiles in children and adolescents. Moreover, NBP607-QIV was more immunogenic against influenza B compared with the control, an egg-based subunit vaccine.